Membraneless enzymatic biofuel cell powered by starch biomass - Aliyah, Jamaludin; Che Ku Mohammad Faizal, Che Ku Yahya (AIP Conference Proceedings, 2022)
This present work reports on an eco-friendly and membraneless enzymatic biofuel cell (EBFC) with direct utilization of starch as biofuel. This study examines the compatibility of Metroxylon Sagu (Sago) starch to be used as a substrate in the production of biofuel in EBFC via enzymatic hydrolysis, which has not yet been explored. The hydrolysis is adapted from the idea of simultaneous saccharification and fermentation (SSF), which is widely used in another biofuel production. Alpha-amylase (ĮAmy) and glucoamylase (Gamy) enzymes (1:1 ratio) are used simultaneously in the hydrolysis process of Sago to produce glucose. Membraneless EBFC makes the biofuel cell less bulky and reduces the cost. The presence of glucose after the hydrolysis process was identified using the DNSA method. Meanwhile, the catalytic currents have been successfully observed in the cyclic voltammetry analysis to confirm the redox reaction. Furthermore, the electrochemical performances of the membraneless EBFC were evaluated in terms of the open circuit voltage (OCV) and the maximum power density. All the measurements were carried out with a potentiostat. The best catalytic currents of an EBFC employing 1.5% (w/v) concentration of Sago substrate and 200 l of enzymes and present a maximum power density of 39.3 W cm-2 and an OCV of 0.32 V. The results proved that the direct use of Sago in EBFC successfully produces biofuel and thus generates electricity. Membraneless EBFC is a potential candidate for low-powered implantable and wearable devices.